PERSEPSI MAHASISWA TERHADAP TRANSPARANSI DAN KEADILAN KEBIJAKAN UANG KULIAH TUNGGAL (UKT) DI UNIVERSITAS NEGERI MANADO - Shelty D. M. Sumual; Joulanda A. M. Rawis; Indra Rianto; Dhea Jessica Sendiang; Rofinus Banunaek (STKIP Pesisir Selatan, 2025)
The misalignment between UKT policy and students' actual conditions has multidimensional impacts. A perceived disproportionate UKT burden not only places a financial burden on families but also creates a psychological burden that can disrupt students' concentration and the continuation of their studies. The implementation of the Single Tuition Fee (UKT) policy often triggers controversy regarding transparency and justice. This study analyzes student perceptions at Universitas Negeri Manado (UNIMA) regarding UKT implementation and its psychological impact. Using a qualitative case study approach, data were collected via in-depth interviews and source triangulation. The findings reveal a dualism in perception which are some students view UKT determination as procedurally compliant, while others rely on fee relaxation mechanisms. Key findings indicate that despite financial anxiety, students exhibit high optimism driven by trust in appeal mechanisms as a form of procedural justice. It is concluded that effective higher education financial management requires procedural flexibility to accommodate students' economic dynamics and ensure study continuity.